2021
DOI: 10.7759/cureus.18882
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Honey: A Promising Therapeutic Agent for Treating Wound Infections

Abstract: Treatment of wounds, especially chronic ones, is a major challenge in healthcare, with serious clinical and economic burdens. Multiple treatment approaches, including the usage of silver and iodine, have dramatically improved wound healing and reduced the incidence of infection. However, once infected by drug-resistant bacteria, treatment of wounds becomes a serious complication, with limited availability of effective antibiotic drugs, leading to high morbidity and mortality. Therefore, alternative therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
(52 reference statements)
0
16
0
Order By: Relevance
“…There is a growing demand to find alternative agents/approaches to replace antibiotics due to the global threat of AMR, which continues to increase despite the limited number of effective antibiotics targeting MDR bacteria [ 1 ]. Consequently, a high demand towards various natural products (NPs) presented with antibacterial activity and mode of action unlike conventional drugs, including honey, was widely observed [ 11 , 18 ]. Honey has been revered and valued as one of nature’s greatest gifts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a growing demand to find alternative agents/approaches to replace antibiotics due to the global threat of AMR, which continues to increase despite the limited number of effective antibiotics targeting MDR bacteria [ 1 ]. Consequently, a high demand towards various natural products (NPs) presented with antibacterial activity and mode of action unlike conventional drugs, including honey, was widely observed [ 11 , 18 ]. Honey has been revered and valued as one of nature’s greatest gifts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that honey can be used to treat wounds, diabetes mellitus, cancer, and cardiovascular, neurological, and gastrointestinal diseases. The antibacterial properties of honey have been studied over the years, and many studies have found that natural honey has some broad-spectrum antibacterial activity towards drug resistant pathogenic bacteria [ 11 ]. Therefore, honey has been considered as a potential bioactive natural product that showed promising activity against pathogenic bacteria to treat a variety of bacterial infections [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P. aeruginosa is not only limited to a local infection in patients with burns (wound infection), but it can disseminate via the bloodstream leading to bacteremia, sepsis, and death [ 24 ]. Wounds and burns are moist environments that are suitable for the establishment and propagation of P. aeruginosa [ 53 ]. Infections caused by P. aeruginosa are usually treated by piperacillin-tazobactam due to the resistance patterns of this bacterium [ 54 ].…”
Section: Discussionmentioning
confidence: 99%